Automated tobacco assessment and cessation support for cancer patients. Issue 4 (25th October 2013) - Warren, Graham W.; Marshall, James R.; Cummings, K. Michael; Zevon, Michael A.; Reed, Robert; Hysert, Pat; Mahoney, Martin C.; Hyland, Andrew J.; Nwogu, Chukwumere; Demmy, Todd; Dexter, Elisabeth; Kelly, Maureen; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Tobacco assessment and cessation support are not routinely included in cancer care. An automated tobacco assessment and cessation program was developed to increase the delivery of tobacco cessation support for cancer patients. METHODS A structured tobacco assessment was incorporated into the electronic health record at Roswell Park Cancer Institute to identify tobacco use in cancer patients at diagnosis and during follow‐up. All patients who reported tobacco use within the past 30 days were automatically referred to a dedicated cessation program that provided cessation counseling. Data were analyzed for referral accuracy and interest in cessation support. RESULTS Between October 2010 and December 2012, 11, 868 patients were screened for tobacco use, and 2765 were identified as tobacco users and were referred to the cessation service. In referred patients, 1381 of those patients received only a mailed invitation to contact the cessation service, and 1384 received a mailing as well as telephone contact attempts from the cessation service. In the 1126 (81.4%) patients contacted by telephone, 51 (4.5%) reported no tobacco use within the past 30 days, 35 (3.1%) were medically unable to participate, and 30 (2.7%) declined participation. Of the 1381 patients who received only a mailed invitation, 16 (1.2%) contacted the cessation program for assistance. Three questions at initial consult and follow‐up generated over 98% of referrals. Tobacco assessment frequency every 4 weeks delayed referral in < 1% of patients. CONCLUSIONS An automated electronic health record‐based tobacco assessment and cessation referral program can identify substantial numbers of smokers who are receptive to enrollment in a cessation support service. Cancer 2014;120:562–569. © 2013 American Cancer Society.